2016
DOI: 10.2807/1560-7917.es.2016.21.46.30403
|View full text |Cite|
|
Sign up to set email alerts
|

Outbreak of enterovirus D68 of the new B3 lineage in Stockholm, Sweden, August to September 2016

Abstract: We report an enterovirus D68 (EV-D68) outbreak in Stockholm Sweden in 2016. Between 22 August and 25 September EV-D68 was detected in 74/495 respiratory samples analysed at the Karolinska University Hospital. During the peak week, 30/91 (33%) samples were EV-D68 positive. Viral protein (VP)P4/VP2 sequencing revealed that cases were caused by B3 lineage strains. Forty-four (59%) EV-D68-positive patients were children aged ≤ 5 years. Ten patients had severe respiratory or neurological symptoms and one died.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 9 publications
7
62
1
5
Order By: Relevance
“…By contrast, EV from species A or B were more frequently detected in upper respiratory tract infections (p < 0.01). Also, there was no significant difference in the proportion of patients from each group admitted to the ICU in contrast to those reported by other authors who observed a higher incidence of severe disease among patients infected by EV-D68 [33,35].…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…By contrast, EV from species A or B were more frequently detected in upper respiratory tract infections (p < 0.01). Also, there was no significant difference in the proportion of patients from each group admitted to the ICU in contrast to those reported by other authors who observed a higher incidence of severe disease among patients infected by EV-D68 [33,35].…”
Section: Discussioncontrasting
confidence: 91%
“…The phylogenetic tree showed that most of the Spanish EV-D68 sequences detected during 2016 clustered to the recently described lineage B3 [33], while strains from 2014 and 2015 belonged to subclade B2. Similar results have been obtained with other studies [34,35], suggesting that all the 2016 outbreaks would be [28][29][30]. These findings indicate that although EV-D68 epidemics can be due to the emergence of new lineages, multiple clades have been circulating simultaneously worldwide from 2010 to the present day.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…During the 2014 EV-D68 epidemic in Europe, most of the 205 sequenced viruses collected in 17 countries in the second semester of the year were found to belong to B1 and B2 clades, whereas A clades, although co-circulating, were detected in a smaller number of patients [31]. Since April 2016, EV-D68 infection outbreaks have been reported in several European countries, particularly in Northern Europe [31][32][33]. Phylogenetic analyses showed that these viruses belonged to the B3 lineage [32].…”
Section: Discussionmentioning
confidence: 99%
“…Between 1970 and 2005, only 26 cases were reported to the CDC and the virus was generally associated with mild upper respiratory illness [8,9].In 2014, unprecedented outbreaks of EV-D68 associated with severe respiratory disease and acute flaccid myelitis emerged throughout the world [3,. Since 2014, there have been biannual patterns of severe disease associated with EV-D68 [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. This unique pattern of recurring outbreaks and severe pathology sheds light on the importance of understanding evolutionary changes in contemporary EV-D68 strains.…”
Section: Introductionmentioning
confidence: 99%